2009
DOI: 10.1167/iovs.08-2501
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Inflow and Outflow Rates Despite Lower IOP in Bestrophin-2-Deficient Mice

Abstract: Purpose Bestrophin-2 (Best2), a putative Cl− channel is expressed in the nonpigmented epithelium (NPE). Disruption of Best2 in mice results in a diminished intraocular pressure (IOP). Aqueous humor dynamics were compared in Best2+/+ and Best2−/− mice, to better understand the contribution of Best2 to IOP. Methods Measurements of IOP, episcleral venous pressure (EVP), conventional outflow facility (Ct), aqueous humor production (Fa), and anterior chamber volume (Va) were made using anterior chamber cannulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 31 publications
3
58
0
Order By: Relevance
“…3B) (11,12). The effect of knocking out Best2 was to decrease IOP despite an increase in F a (11,13). Measurement of aqueous dynamics in those mice demonstrated that both C t and C u were increased to more than compensate for the increase in F a .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3B) (11,12). The effect of knocking out Best2 was to decrease IOP despite an increase in F a (11,13). Measurement of aqueous dynamics in those mice demonstrated that both C t and C u were increased to more than compensate for the increase in F a .…”
Section: Discussionmentioning
confidence: 99%
“…IOP and aqueous dynamics measurements were performed 3-4 h later and always between 2:00 and 6:00 p.m. to avoid diurnal pressure variations. Measurement of IOP, episcleral venous pressure (EVP), F a , and C t were made by cannulation of the anterior chamber with borosilicate glass microneedles as described previously (13,21) in mice anesthetized with Avertin (300 mg/kg injected intraperitoneally). C u was calculated using measured parameters according to the modified Goldmann equation:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we worked under the hypothesis that absence of Best2 would cause increased IOP due to an increase in intracellular bicarbonate in NPE cells, we found the opposite; that Best2 -/ -mice have a significantly lower IOP than their wild-type (WT) littermates. 17,18 A more detailed examination of aqueous dynamics in the mice revealed that they do indeed produce more aqueous humor than their Best2 + / + littermates in a given span of time. 18 However, C t and F u are increased sufficiently to overcompensate for the increase in aqueous production.…”
Section: Bestrophinsmentioning
confidence: 99%